(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The main focus of this research was to enhance the strength of soil & to get an optimum amount of soil- fly-ash –Recon 3s mix. The target of study was to extend the strength of clayey soil using ash &Recron3s. As we all know ash act as a cement material & Recon 3s act as a reinforcing material. As clay shows high shrinkage, swell characteristics & low bearing capacity. There is a necessity to enhance the strength characteristics. Therefore the main focus of this research was to extend the strength characteristics of soil. The tests performed in laboratory was Pyconometer test for relative density casagrande’s test for liquid limit, plastic limit test, Standard proctor test for determination of OMC & MDD, unconfined compression test & Direct shear test. Proportional of the recon 3s used was 0.2, 0.4, 0.6, 0.8 & 1.0 try to proportional of ash was 10, 15,20,30,40 & 50%. The ash was optimized at 15% & UCS value for virgin soil was 215.6KN/m2& by adding ash in numerous proportions i.e., 10, 15, 20,30,40,50. The UCS values were 409.10, 460.1, 378.7, 345.2, 242.01 & 234.06 in KN/m2 that the maximum was at 15% fly ash. After adding Recron3s in several proportions i.e., 0.2, 0.4, 0.6, 0.8 & 1.0 %. The UCS values were 512.46, 566.49, 625.23, 672.1 & 654.35 in KN/m2 for 1 week curing. Therefore, the maximum was at 0.8% & for two weeks curing UCS values was 587.085, 625.23, 676.81, 710.2 & 672 in KN/m2 & again was maximum for 0.8%. The results of direct shear test for virgin soil was - cohesion intercept 24.6 KN/m2 & angle of shearing resistance 19.20 & was increased by adding ash & Recron3s at 15% ash & 0.8% Recron3s it had been 62.2 KN/m2 & 29.10.From this study it absolutely was concluded ash works as a cementing material & Recron3s as a reinforcing material & provides strength to the soil in addition as fly ash .the most effective proportion obtained was; 84.2% soil – 15% ash – 0.8% recon 3s. Also, the tactic utilized in this research was randomly distributed fiber reinforcement soil also turned as RDFS. Also, from Proctor test it had been found that OMC increases & MDD decreases with increase in fly ash & recon 3s.